Development of Online Science Learning Devices Cooperative Model Type STAD Assisted by Video Media to Improve Learning Outcomes of Elementary School Students - Hariyati; Budi Jatmiko; Raharjo (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2020)
The research aims to produce STAD cooperative model online learning tools with the help of video media to improve student learning outcomes in elementary schools. The development of learning tools used the 4D model and was tested on 40 students. The results showed that online science learning tools were valid with validation results in the very valid category (84.9%) and Student Teaching Materials (96%); practical in terms of implementing RPP (87.26) is categorized as very good and obstacles during learning can be overcome; effective in terms of positive student responses (88.89%), student activity (91.76%) is categorized as very good, and student learning outcomes increase knowledge competence with an average N-gain of 0.75 in the high category. In the Independent T-test, the 2-way significance value of 0.456> 0.05 indicates that there is no difference in the average learning outcomes between groups. then on the t-pair Sig. (2-tailed) 0.000 <0.005 indicates an increase in learning outcomes. The conclusion of this study, that the online STAD IPA cooperative learning model assisted with developed video media is appropriate to be used to improve learning outcomes of elementary school students.